Adultery Outside of Marriage Regulated in the KUHP - Moh. Soleh; Nabilah Rohmah Trismianti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Many factors cause divorce in marriage, one of which is due to intercourse outside the marriage bond, so between the two parties one or even both of them have intercourse outside the marriage bond with other people outside their marriage. Basically, adultery can occur due to a decrease in the morality of every human being. The moral damage that is happening today is due to the increasing number of sexual acts. Sexual intercourse outside the marriage bond is an act of sexual intercourse between a man and a woman who are not bound by marriage (marriage). Adultery in Indonesian Criminal Law is regulated in Article 284 of the Criminal Code (KUHP) such harsh sanctions. Meanwhile, in the 2015 Criminal Code Bill regulation, it is stated that not only people who are already bound in marriage can be convicted for committing adultery. This is explained in the 2015 Criminal Code Bill Article 483 paragraph (1) letter e.